2014
DOI: 10.5137/1019-5149.jtn.8671-13.0
|View full text |Cite
|
Sign up to set email alerts
|

Anterior pituitary hormone deficiency in subjects with total and partial primary empty sella: do all cases need endocrinological evaluation?

Abstract: AIm:To compare anterior pituitary functions between subjects with total and partial primary empty sella (PES) and to assess whether all cases with PES need endocrinological evaluation. mATERIAL and mETHods: Eighty-one subjects with PES (34 total and 47 partial) were included in the study. Basal anterior pituitary and its target hormones were assessed and those with low insulin like growth factor-1 and/or low basal cortisol levels underwent insulin tolerance test (ITT).REsuLTs: 67.4% of the subjects with total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 11 publications
2
31
1
5
Order By: Relevance
“…In five studies involving a total of 343 patients with empty sella, the prevalence of central hypothyroidism was 0-22.2%. [34][35][36][37][38] However, it should be noted that the studies with the highest prevalence of central hypothyroidism (14.3% and 22.2%, respectively) were either a retrospective analysis 34 or analyzed patients admitted to the hospital 38 and, thus, may overestimate the prevalence. The other three studies involving a total of just 87 patients showed a combined prevalence of central hypothyroidism of just 3.4%.…”
Section: Hypothalamic And/or Pituitary Diseasementioning
confidence: 99%
“…In five studies involving a total of 343 patients with empty sella, the prevalence of central hypothyroidism was 0-22.2%. [34][35][36][37][38] However, it should be noted that the studies with the highest prevalence of central hypothyroidism (14.3% and 22.2%, respectively) were either a retrospective analysis 34 or analyzed patients admitted to the hospital 38 and, thus, may overestimate the prevalence. The other three studies involving a total of just 87 patients showed a combined prevalence of central hypothyroidism of just 3.4%.…”
Section: Hypothalamic And/or Pituitary Diseasementioning
confidence: 99%
“…Basándose en la naturaleza de la función hipofisaria se han realizado diversos trabajos que describen la sintomatología endocrina por la herniación del diafragma selar sobre la hipófisis 2,14 ; se sabe que existe una asociación entre el grado de herniación, ya sea parcial o total, y el grado de hipopituitarismo 4,20 . El desbalance que produce el líquido cefalorraquídeo sobre las estructuras cerebrales involucradas altera su función; la situación del área selar y estructuras cercanas, como el tallo cerebral, de donde emergen diversos pares craneales, puede incidir en la presentación de un conjunto de signos relacionados con los núcleos y con el origen aparente de los pares craneales.…”
Section: Discussionunclassified
“…Other causes include pituitary apoplexy, postpartum pituitary necrosis [Sheehan's syndrome (SS)], empty sella, stroke, traumatic brain injury (TBI), subarachnoid hemorrhage (SAH), and lymphocytic hypopituitarism [1][2][3][4][5][6][7][8][9]. Primary empty sella (PES) is defined as the thinning of the pituitary gland after subarachnoid space herniated into the sella turcica in patients with no history of pituitary tumor, radiotherapy, and surgery [4][5][6]10]. It occurs due to SS or lymphocytic hypophysitis [5,6].…”
Section: Introductionmentioning
confidence: 99%